YOUTH CENTER KALIMANTAN BARAT DI KUBU RAYA - Sandy, Sandy; Purnomo, Yudi; Affrilyno, Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
Adolescence is a transitional phase from childhood to adulthood. Teenagers require dedicated facilities where they can gather, engage in discussions, and share ideas. A significant issue in fostering youth creativity is the lack of adequate infrastructure and facilities for teenagers in West Kalimantan. One solution to this issue is the development of a Youth Center. The Youth Center of West Kalimantan, located in Kubu Raya, is designed to accommodate three main functions—education, recreation, and sports—aiming to support the development of skills, creativity, and social interaction among youth. The design method employed refers to R. Whitaker approach, which includes the stages of introduction, definition, preparation, analysis, synthesis, evaluation, and reevaluation. The result achieved in designing this building is a single-mass structure that adopts a comfortable and adaptive communal space concept, which is applied across several areas of the building.. The result of this design process is a communal space that serves as a platform for social interaction, allowing teenagers to engage in various activities together.